Proposal of research seedbeds for the development of research competence in engineering - Guerrero Hernández, V.; Lagunes Domínguez, A.; Torres Gastelú, C.A.; Lau Noriega, J. (Nexo Revista Científica, 2019)
This paper deals with the importance of research competence in university students studying some engineering and a proposal for their development. The methodology used was developed in three phases, the first phase consisted of identifying the problem of lack of research in the countries of Latin America, for this purpose, research rankings, rankings of research centers and ranking of universities were analyzed, because they are the spaces where research should be developed in each country. The second phase consisted of making the state of the art about the efforts made in each country to achieve research competence. The third phase was the description of the proposal of research seedbeds for the development of said competence. The main result was the proposal of research seedbeds for the development of the research competence in engineering, which is being applied at this moment. In conclusion we have that the binomial of the research nurseries and the combined learning will allow to develop the research competence in engineering students.